Telaah Konseptual atas Berbagai Model Pengukuran Earnings Management: Edisi Revisi - Suyono, Eko; Sunarmo, Agus; Sugiarto, Sugiarto; Budianto, Roni (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
As explained by Healy and Wahlen (1999), earnings management occurs when managers use judgment in financial reporting and in structuring transactions to alter financial reports to either mislead some stakeholders about the underlying outcomes that depend on reported accounting numbers or to influence contractual outcomes that depend on reported accounting numbers’. Several accounting researchers have proposed models for detecting the earnings management, e.g, Healy model (1985), De Angelo model (1986), Jones model (1991), Industry model (1991), Modified Jones Model (1995), Dechow & Dichev model (2002), Kothari Model (2005), Classification Shifting Model (McVay, 2006), Stubben Model (2010), the new approach model (2011), etc. This study aims to evaluate those of earnings management models, which is the most accurate in measuring earnings management. After comparing those earnings management models, this study concludes that the new approach model is able to overcome the weaknesses in other models, thus, so far it is the most accurate model in measuring the earnings management.